Population pharmacokinetics and exposure–response relationships of maribavir in transplant recipients with cytomegalovirus infection - Ivy H. Song; Grace Chen; Siobhan Hayes; Colm Farrell; Claudia Jomphe; Nathalie H. Gosselin; Kefeng Sun (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
Maribavir is approved for management of post-transplant cytomegalovirus (CMV) infections refractory and/or resistant to CMV therapies at a dose of 400 mg twice daily (BID). Population pharmacokinetic (PopPK) and exposure–response analyses were conducted to support the appropriateness of 400 mg BID dosing. A PopPK model was developed using non-linear mixed-effects modeling with pooled maribavir plasma concentration–time data from phase 1 and 2 studies (from 100 mg up to 1200 mg as single or repeated doses) and the phase 3 SOLSTICE study (400 mg BID). Exposure–response analyses were performed for efficacy, safety, and viral resistance based on data collected in the SOLSTICE study. Maribavir PK after oral administration was adequately described by a two-compartment model with first-order elimination, first-order absorption, and an absorption lag-time. There was no evidence that maribavir PK was affected by age, sex, race, diarrhea, vomiting, disease characteristics, or concomitant use of histamine H 2 blockers, or proton pump inhibitors. In the SOLSTICE study, higher maribavir exposure was not associated with increased probability of achieving CMV DNA viremia clearance, nor with reduced probability of treatment-emergent maribavir-resistant CMV mutations. A statistically significant association with maribavir exposure was identified for taste disturbance, fatigue, and treatment-emergent serious adverse events, while transplant type, enrollment region, CMV DNA level at baseline, and/or CMV resistance at baseline were identified as additional risk factors for these safety outcomes. In conclusion, the findings of these PopPK and exposure–response analyses provide further support for the recommended maribavir dose of 400 mg BID.

Modeling and Simulation Support Eltrombopag Dosing in Thrombocytopenic Patients with Chronic HCV Infection - Jianping Zhang; Mita Thapar; Colm Farrell; Mary B. Wire (Pharmaceutical Research, 2015)

Challenges and Opportunities in Establishing Scientific and Regulatory Standards for Assuring Therapeutic Equivalence of Modified Release Products: Workshop Summary Report - Mei-Ling Chen; Vinod P. Shah; Derek Ganes; Kamal K. Midha; James Caro; Prabu Nambiar; Mario L. Rocci; Avinash G. Thombre; Bertil Abrahamsson; Dale Conner; Barbara Davit; Paul Fackler; et al. (The AAPS Journal, 2010)